Quantum core affect. Color-emotion structure of semantic atom - Surov, Ilya A. (Frontiers in Psychology, 2022)
Psychology suffers from the absence of mathematically-formalized primitives. As a result, conceptual and quantitative studies lack an ontological basis that would situate them in the family of natural sciences. The paper addresses this problem by describing a minimal psychic structure, expressed in the algebra of quantum theory. The structure is demarcated in categories of emotion and color, renowned as elementary psychological phenomena. This is achieved via quantum-theoretic qubit state space, isomorphic to emotion and color experiences both in meaning and math. In particular, colors are mapped to the qubit states via geometric affinity between the HSL-RGB color solids and the Bloch sphere, widely used in physics. The resulting map aligns with the recent model of affective meaning, producing a unified color-emotion sphere of subjective experience. The obtained structure is identified as a semantic atom of natural thinking - a unit of affectively-colored personal meaning, involved in elementary acts of binary decision. The model contributes to finding a unified ontology of both inert and living Nature, bridging previously disconnected fields of research. In particular, it enables theory-based coordination of emotion, decision, and cybernetic sciences, needed to achieve new levels of practical impact.